Fairy godmothers, Inc. - DeWylde, Saranna (DeWylde, Saranna. Fairy godmothers, Inc., 2021)
If love is the source of all the magic in the universe, and the town of Ever After, Missouri, is the epicenter of enchantment, then the locals are in dire need of a reboot. At least according to resident fairy godmothers Petunia, Jonquil, and Bluebonnet. Their solution? Blow a bit of fairy dust in the direction of those in need of romance...What could possibly go wrong?